Analisis Kebutuhan Bahan Ajar Matematika untuk Menstimulus Kemampuan Literasi dan Numerasi di Tingkat Sekolah Dasar - Ningrum, Izza Eka; Widodo, Aris; Fonda, Aulia (AS-SABIQUN, 2025)
Students' requirements are not as well met by the teaching resources that are currently on the market. The majority of instructional materials tend to emphasize memorization of abstract ideas without giving detailed context. As a result, students show little interest in and comprehension of the subject matter being taught. PISA and AKM show low numeracy literacy skills in students. This study examines Babat's SD Muhammadiyah 2's math teaching resource needs for numeracy literacy. This study uses quantitative descriptive methods. The study found that current teaching materials are not improving students' numeracy literacy skills. Up to 8% of students are very low, 42% are low, 26% are medium, 21% are high, and 3% are very high. Students like using colorful instructional materials and find LKPD fun for arithmetic.